TINJAUAN UMUM TENTANG PENDIDIKAN ISLAM - Chotimah, Chusnul (TA'LIMUNA: Jurnal Pendidikan Islam, 2013)
Understanding of the concept of Islamic education is absolutely necessary for the formulation and development of Islamic education system. Characteristics of Islamic education consist of at least three things: first, based on al-Qur'an and al-Hadith, or departed from the spirit of Islam. Second, the concept of operations can be analyzed and developed from the process of familiarization, the inheritance and development of Islamic values, regardless of the value dichotomy and secularism, while the third, practical concepts can be understood, analyzed and developed from the process of coaching and personal development of Muslims in every generation. In term of subject, Islamic education emphasize on seeking knowledge on the basis of God obedience (ibadah), moral values, recognition of the potential and ability to become a personality advancement and the practice of science on the basis of responsibility to God and man. This is the characteristic that distinguishes education with education in general characteristics.